Design development of UP Mindanao Integrated Information System purchase request information subsystem - Debil, Ozzie Faelnar (2006)
This special problem developed a subsystem with two database-driven applications that are designed to facilitate the process of supply and property requisition and purchasing of the Supply and Property Management Office of the University of the Philippines in Mindanao. The applications have a user-friendly graphical user interface, eliminated redundancy of encoding data, provided mechanism to eliminate typographical errors, and the automation of processes involved. This subsystem was developed for use by the employees of the university who are concerned in requisition and purchasing of supplies, materials and equipment. The subsystem was designed to operate jointly with the other subsystems of the UP Mindanao Integrated Information Management System. The applications were implemented in Java making them a platform-independent application while its database was built using MySQL database server
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2006
Keywords: UP in Mindanao Integrated Information Management System; Purchasing and supply management; eRPortal materials management; Bulacan Information System; System architecture design